1999
DOI: 10.1111/j.1745-9125.1999.tb00504.x
|View full text |Cite
|
Sign up to set email alerts
|

In the Company of Women: Structure and Agency in a Revised Power‐control Theory of Gender and Delinquency*

Abstract: A power‐control theory of the gender‐delinquency relationship draws attention to differences in familial control practices. We extend the theory to address how parental agency and support for dominant attitudes or schemas influence male as well as female delinquency. This extension emphasizes that differences in structure, particularly between more and less patriarchal households, result in different family practices, especially for mothers and sons. We find that variation in mothers' agency within the home af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
61
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 65 publications
(63 citation statements)
references
References 25 publications
2
61
0
Order By: Relevance
“…Previous research that has examined cultural differences in parenting has found that socioeconomic factors have a stronger impact on parental social control than cultural factors [118] but in this study we do not control for class. We also expect this to relate to the fact that the sample of Indonesian youths were drawn from major cities in Indonesia, where the power-control dynamic between parents may resemble balanced households in the U.S. [71]. Therefore, we do not find support for Hypothesis 5.…”
Section: Gender and Place As Modifiersmentioning
confidence: 71%
See 4 more Smart Citations
“…Previous research that has examined cultural differences in parenting has found that socioeconomic factors have a stronger impact on parental social control than cultural factors [118] but in this study we do not control for class. We also expect this to relate to the fact that the sample of Indonesian youths were drawn from major cities in Indonesia, where the power-control dynamic between parents may resemble balanced households in the U.S. [71]. Therefore, we do not find support for Hypothesis 5.…”
Section: Gender and Place As Modifiersmentioning
confidence: 71%
“…First, patriarchal families involve hierarchical structures through which parental control is exercised differentially through male domination. The assumption is that men have higher class positions in patriarchal families, and this imbalance provides fathers with greater resources to establish male dominance [71]. Parents exercise more control over daughters than sons, which allows daughters to become more risk averse and less likely to engage in delinquent acts.…”
Section: Parental Social Control and Self-reported Violent Delinquencymentioning
confidence: 99%
See 3 more Smart Citations